Implementing educational policies at micro level: an analysis from the school professionals in the practice context - Breynner Ricardo de Oliveira (Red Latinoamericana de Estudios Epistemológicos en Política Educativa, 2019)
This article analyzes the school professionals as public policies implementer agents from a political perspective, taking as reference the researches of Ball (1987, 2002, 2005), Ball et al. (2012); Michael Lipsky (1980); Maurice Tardif (2002); Lessard and Carpentier (2016), Oliveira (2014) and Gussi and Oliveira (2016). Despite of starting from different theoretical and methodological contributions, such references have a critical view of the Weberian conception about bureaucracy and the role played by bureaucrats in the public policies implementing process. It´s intended to use such literature to think the educational policies and the actors that daily act in this process at a local level. Assuming that implementation is a political process and the actors involved in this process have different agendas and interests, the discussion for the educational policies field assumes that educational institutions are complex, in which the base agents interactions and actions help unravel the dynamics that are built there. As the public policies are not announced in the same way, different meanings will be attributed along their trajectory to the local level, reason why the interpretation and translation concepts are important.